Toll-like receptors (TLRs) and T cell effector function - Mahmood, Majid Mohammed (2020)
The aim of the project was to identify whether cattle T cell subsets express toll-like receptors (TLRs), and if so whether there was any functional consequence of this when they were stimulated with TLR-ligands. CD4+ T cells, CD8+ T cells, and γδ T cells were studied in the context of whole PBMC or as isolated cells. To develop rabbit Tregs as a source of cells to study expression of toll-like receptors (TLRs), putative rabbit regulatory T cells (Tregs) were developed as cultured cells from MLN as part of an ongoing project and to inform generation of cattle Treg development for this study. Culture of rabbit MLN cells resulted in detection of CD4+CD25hiFOXP3+ (putative nTregs) in about one fifth of the total cells. The cultured rabbit Tregs did not exhibit any immunosuppressive effect on autologous MLN (Mesenteric lymph node) cells in a suppression assy. This and the complexity of this method meant that the cattle Treg work was not initiated for this study.